Study of Gender Differences in Proton Pump Inhibitor Dose Requirements for GERD: A Double-Blind Randomized Trial. - Helgadóttir, Hólmfridur; Metz, David C; Lund, Sigrún H; Gizurarson, Sveinbjorn; Jacobsen, Elin I; Asgeirsdóttir, Gudrún A; Yngadóttir, Yrsa; Björnsson, Einar S (Journal of Clinical Gastroenterology, 2017)
To access publisher's full text version of this article click on the hyperlink below To determine the proportion of patients with gastroesophageal reflux disease who are on proton pump inhibitors (PPIs) who could reduce their prior dosage by half, and identify predictors of successful step-down. Appropriate hypergastrinemia results from gastric acid inhibition. A gender difference in fasting gastrin with higher levels among women than among men on long-term PPI therapy has been demonstrated. Patients with endoscopically verified erosive esophagitis on long-term PPI therapy were randomized double blindly to step down their dose by half or continue with the same dose for 8 weeks. Fasting gastrin levels were measured before and after treatment. The primary endpoint was successful step-down throughout the study period. Overall, 100 patients were randomized, 49 (24 females) to continue with the same dose as before and 51 (25 females) to step down. Female patients had higher gastrin levels compared with male patients: 78 pg/mL (IQR, 50 to 99) versus 50 pg/mL (IQR, 36 to 74) (P=0.007). Among those randomized to the step-down intervention only 3/25 (12%) women failed to complete the 2 months of lower-dose therapy versus 9/25 (36%) men (P=0.09). Female gender (P=0.048) was the strongest predictor for successful step-down (odds ratio=1.27; 95% CI, 1.01-1.60). The chance of failing to maintain symptom control was twice as high in the reduction group (24%) as compared with the control group (13%) (P=0.2). Female patients on long-term PPI therapy were 3 times more likely to tolerate half of their prior dose. Female gender had higher probability for successful step-down. These results indicate that women with gastroesophageal reflux disease might manage with lower doses of PPIs as compared with men.European Clinical Trial Database (https://eudract.ema.europa.eu/), number 2013-002067-26. National Institutes of Health Research Fund of the National University Hospital of Iceland Icelandic Research Fund